Increasing inequalities in what we do online: A longitudinal cross sectional analysis of Internet activities among the Dutch population (2010 to 2013) over gender, age, education, and income - van Deursen, Alexander J.A.M.; van Dijk, Jan A.G.M.; ten Klooster, Peter M. (Telematics and informatics, 2015)
•We investigate online activities among a representative sample (NL) from 2010 to 2013.•Capital enhancing activities were relatively popular among men and younger people.•These activities were also popular among those with higher education and income.•Changes in the distribution of demographics between 2010 and 2013 were observed.•There is increasing capital for those with higher education and income. We investigate types of Internet activities among a representative sample of the Dutch population from 2010 to 2013. We examined usage patterns of seven types of Internet activities (i.e., information, news, personal development, commercial transaction, social interaction, leisure, and gaming) and related these patterns with gender, age, education, and income. Activities related to news, personal development, commercial transaction, and social interaction increased in popularity. For most capital enhancing activities, men, younger people, higher educated people, and people with higher than average incomes were prominent. These observations, however, are subject to change. The Internet seems to provide increasingly more capital-enhancing opportunities for those with higher education and income, which would accordingly reinforce their already strong positions in society.